Real life data on the biopsychosocial effects of Adalimumab in the management of hidradenitis suppurativa: A multicenter cross sectional analysis and consideration of a multisystem monitoring approach to follow up. Issue 1 (5th January 2021) - Muralidharan, Vijaytha; Pathmarajah, Pirunthan; Peterknecht, Elizabeth; Qazi, Erma; Barlow, Richard; Muralidharan, Vivek; Abdullah, Anthony; McDonald, Bryan; Bewley, Anthony
Abstract: Hidradenitis suppurativa (HS) is a chronic relapsing, remitting disease which results in the formation of inflammatory nodules and pustules in intertriginous areas. HS is a complex disease with known psychosocial impact. Adalimumab is a biologic, used for treatment resistant HS, which working by inactivating TNF‐alpha. Our primary objective was to determine the effects of adalimumab on HS‐PGA and DLQI scores in patients with HS that had been on the treatment for at least 6 months. Our secondary objective was to note and assess the significance of adverse effects and impacts on wider health, namely occupational and social. A retrospective cross‐sectional study was performed using clinic notes from routine follow ups in biologic clinics in three specialist HS centers. About 77% (n = 78/101) patients demonstrated improvements in their HS‐PGA scores. Significant improvements in the DLQI scores of the patient cohort ( P = .0001, 95% CI −12.8 to −5.9) have also been demonstrated. A total of 31.7% (32/101) patients experienced adverse effects spanning multiple organ systems, with 27.7% (28/101) requiring treatment cessation. Three of these patients stopped due to the worsening of preexisting mental health symptoms. Adalimumab is effective in reducing HS‐PGA and DLQI scores, but patients still complain of systemic effects necessitating drug cessation in some instances. A holistic and multisystemic approach to follow up is required, and there is scope for further studies examining temporal causality in the context of adalimumab and its multisystemic physical and psychological effects.